Fortification of baked products with soy protein: studying the effects of baking with soy protein and potential use in the development of hands-on food science education modules - Brown, Janae (Kansas State University, 2022)
Soy protein ingredients are of interest for the development of high-protein bakery foods because soy is a plant-based protein that contains adequate amounts of all essential amino acids. Fortification of bakery foods with soy protein results in changes to physical properties (water absorption, volume, color, and texture) and organoleptic properties (flavor, aftertaste). Research is ongoing to explore methods for improving physical and organoleptic properties of bakery foods with added soy protein to improve consumer acceptance. Enzymatic hydrolysis breaks down proteins into smaller molecular weight peptides with different properties than their large molecular weight counterparts. Soy protein hydrolysates prepared using papain and Flavourzyme have been found to have acceptable sensory properties, however, research is needed to determine the effects of soy protein hydrolysates in food systems. The objective of this study was to observe the effect of soy protein hydrolysates on physical properties of muffins. Seven muffin treatments were prepared in a 2x3 augmented factorial treatment structure. Three protein types (soy protein isolate (SPI), papain soy hydrolysate (PSH), Flavourzyme soy hydrolysate (FSH)) were tested at two levels (10%, 20%). Additionally, a control treatment was prepared with no added protein. Batter tests included specific gravity and pH. Muffin tests included crust and crumb color, height, weight, texture profile analysis, water activity, and moisture loss. Specific gravity ranged from 0.95-1.08 with SPI10, SPI20, and FSH20 having lower (p<0.05) specific gravity values than C. Batter pH ranged from 6.53-7.72 and no significant differences were found. No significant difference was found for crust lightness (70.86-74.49), crumb lightness (72.73-74.77), weight (68.2-72.1 g), hardness (6.85-11.17 N), water activity (0.500-0.580) or moisture loss (11.1-12.7%). Muffin height ranged from 41.7-46.7mm and all treatment heights were similar to control, however, PSH10 and SPI20 were significantly different from each other with heights of 41.7mm and 46.7mm, respectively. Overall, hydrolysis of SPI resulted in batters more similar to control than SPI and did not reduce physical quality as compared to C. Hands-on laboratory exercises play an integral role in STEM education to increase knowledge of core content and facilitate the development of soft skills such as communication skills and the ability to apply knowledge. As enrollment in online courses increases, instructors of STEM courses are challenged with ensuring hands-on learning experiences are available to online students. Additionally, hands-on activities present an opportunity to students to engage with relevant issues faced in the industry to better prepare them for employment upon graduation. The addition of soy protein to bakery foods is a current issue in the food industry that can be used in the development of a hands-on at-home laboratory for online food science students. The objective of this study was to develop an at-home laboratory exercise for online students in an undergraduate food processing lab and compare student perception and performance to a similar on-campus course. Laboratory kits containing a control muffin mix with no soy, a 50% soy flour muffin mix, and 100% soy flour muffin mix were sent to students enrolled in an undergraduate food processing course. Students prepared muffin mixes and scored muffin physical and organoleptic properties using a muffin scorecard. Students completed post-laboratory questions and wrote a scientific abstract to communicate their results. After completion of the module, students responded to a module reflection survey with a 5-point Likert scale. Seventy-two percent of online students met or exceeded expectations on the abstract assignment. Ninety percent of online students agreed or strongly agreed the laboratory improved their ability to apply knowledge to practical issues in food processing and 97% agreed the laboratory exercise improved their scientific communication skills. Student performance and perception results indicate the module was effective in teaching course content and facilitating the development of soft skills. Secondary education teachers use materials outside the curriculum to supplement existing material and to increase student engagement with novel lessons. Supplemental lessons come from a variety of sources, however, the creation of supplemental materials that build on curriculum standards would benefit teachers. The objective of this study was to develop and test a module with hands-on laboratory exercise for use in secondary food and agriculture classrooms. A module was designed and a preliminary test was conducted in a local high school classroom. After modifications were made, an independent teacher-based trial was conducted and a module evaluation survey was sent to teacher participants. While survey response was relatively low (n=3), the module was well-received by respondents.
Keywords: Food; Education; Hands-on; Soy; Hydrolysis; Baking